2020
DOI: 10.1111/ppl.13214
|View full text |Cite
|
Sign up to set email alerts
|

The role of solute transporters in aluminum toxicity and tolerance

Abstract: The prevalence of aluminum ions (Al3+) under acidic soil conditions inhibits primary root elongation and hinders plant growth and productivity. Al3+ alters the membrane potential, displaces critical ions in the apoplast and disrupts intracellular ionic concentrations by targeting membrane‐localized solute transporters. Here, we provide an overview of how Al3+ affects the activities of several solute transporters especially in the root. High Al3+ level impairs the functions of potassium (K+), calcium (Ca2+), ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 94 publications
(144 reference statements)
0
19
0
Order By: Relevance
“…The accumulation of free aluminum (Al 3+ ) ions in the soil solution under low pH limits plant growth and productivity [ 124 ]. Ramesh et al [ 101 ] have monitored malate efflux in roots of near-isogenic, Al 3+ tolerant (ET8) and sensitive (ES8) lines of wheat.…”
Section: Gaba Signaling and Its Response To Abiotic Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…The accumulation of free aluminum (Al 3+ ) ions in the soil solution under low pH limits plant growth and productivity [ 124 ]. Ramesh et al [ 101 ] have monitored malate efflux in roots of near-isogenic, Al 3+ tolerant (ET8) and sensitive (ES8) lines of wheat.…”
Section: Gaba Signaling and Its Response To Abiotic Stressmentioning
confidence: 99%
“…While the GABA level is higher in ET8 than in ES8 under acidic conditions, Al 3+ reduces the GABA level in both lines to similar levels. This suggests that high endogenous GABA inhibits the activity of TaALMT1 in the absence of Al 3+ , and that both malate and GABA are exported from the cytosol when TaALMT1 is Al 3+ activated, resulting in the sequestration of Al 3+ and modulation of the plant sensitivity to Al 3+ [ 102 , 124 ]. Table 2 summarizes various examples wherein ALMT1 overexpression enhances the efflux of malate in response to Al 3+ treatment under acidic conditions [ 101 , 125 , 126 , 127 , 128 ].…”
Section: Gaba Signaling and Its Response To Abiotic Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have showed that the transportation of other ions could also alleviate Al toxicity [19]. For example, Ca 2+ serves as an essential second messenger to modulate developmental plasticity in plants, which reduces the concentration of active Al and fixation of P under Al stress [111,112]. Treatment with higher Ca 2+ concentration alleviates Al-induced inhibition of root growth, which is attributed to higher cytosolic Ca 2+ concentrations through specific Ca 2+ signatures triggering downstream responses [113].…”
Section: Internal Tolerance Mechanismsmentioning
confidence: 99%
“…Downregulation of cellulose and upregulation of callose, oxidative stress, hormones, and DNA damage signaling all result in root growth inhibition (Sade et al, 2016). The plasma membrane is another frequent target, where Al disrupts membrane potential and membrane-bound solute transporters, affecting symplastic and apoplastic concentrations (Kar et al, 2021). Damage within proteins and DNA reduces enzymatic activity and can trigger cell cycle checkpoints.…”
Section: Characterization Of Aluminum Response In a Saccharum Stem Tissuementioning
confidence: 99%